Quantitative Analysis of Copy Number Variants Based on Real‐Time LightCycler PCR. (2nd April 2014) - Ma, Lijiang; Chung, Wendy K.
Abstract: Quantitative real‐time PCR is PCR visualized in real time by the use of fluorescent or intercalating dyes, which are employed to measure gene expression or gene quantification including contiguous gene deletions or duplications. A simple method is described here to quantify DNA copy number from human samples. Curr. Protoc. Hum. Genet . 80:7.21.1‐7.21.8. © 2014 by John Wiley & Sons, Inc.